Weft knitted loop geometry of glass and steel fiber fabrics measured with X-ray micro-computer tomography. Issue 5 (March 2014) - Harjkova, Galina; Barburski, Marcin; Lomov, Stepan V.; Kononova, Olga; Verpoest, Ignaas
X-ray micro-computer tomography (micro-CT) provides 3D visualization of internal geometry of a textile without destructing samples. The objective of this paper is to demonstrate usage of the micro-CT technique for structural analysis of weft-knitted fabrics and to propose a data processing technique for reconstruction and visualization of the loop geometry. The method is applied to glass and steel knitted fabrics. It produces a full description of the loop geometry, namely yarn middle line, cross-section areas and orientation along the yarn.